PENGARUH KOMPENSASI TERHADAP MINAT MELAMAR PEKERJAAN DENGAN LOKASI KANTOR SEBAGAI VARIABEL MODERATING (STUDI PADA PENGGUNA JOBSTREET DI DEPOK) - Gisheila, Margaretha Vira; Utomo, Wahyudi; Hadikusuma, Riza (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2024)
This study aims to analyze the influence of compensation on job application interest with office location as a moderating variable among Jobstreet platform users in Depok. The data collection method used questionnaires with a sample of 100 respondents and was processed using the PLS-SEM analysis method. The data analysis results show that compensation has a positive and significant influence with a path coefficient value of 0.614 and P values of 0.000 on job application interest. The office location variable also has a positive and significant influence with a path coefficient value of 0.293 and P values of 0.001 on job application interest. Additionally, office location is proven to moderate the relationship between compensation and job application interest with a path coefficient value of 0.200 and P values of 0.012. These findings indicate that a strategic office location can strengthen the relationship between compensation and job application interest. The implications of this study are that companies on Jobstreet platform need to consider not only competitive compensation but also strategic office locations to attract job applicants' interest.